2016
DOI: 10.1080/00952990.2016.1185433
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use among Hispanic college students along the US/Mexico border

Abstract: Previous research indicates that greater acculturation is linked to greater consumption of alcohol; however, we found it to be associated with less consumption. The findings regarding gender represent some consistencies with previous research but there are some inconsistencies as well. These results suggest that less acculturated Hispanic male college students residing in the border region may be at a higher risk of alcohol abuse than Hispanic female students and more acculturated male students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Our findings support the notion that cultural orientations operate differently for Hispanic college students living at the U.S.-Mexico border than they do Hispanics living elsewhere (Montoya et al, 2016). Similar to another study with border Hispanics (Pinedo et al, 2017), heritage cultural orientation was not associated with alcohol consumption or negative drinking consequences.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings support the notion that cultural orientations operate differently for Hispanic college students living at the U.S.-Mexico border than they do Hispanics living elsewhere (Montoya et al, 2016). Similar to another study with border Hispanics (Pinedo et al, 2017), heritage cultural orientation was not associated with alcohol consumption or negative drinking consequences.…”
Section: Discussionsupporting
confidence: 90%
“…The acculturation process is nuanced across individuals and critically depends on the sociocultural and physical environments surrounding the individuals (Berry, 2003;Borstein, 2017). Because U.S. and Hispanic cultures may be less differentiated at the U.S.-Mexico border than other parts of the U.S., cultural orientations conceivably do not operate similarly as they do in regions of the U.S. that are further from the border (Montoya et al, 2016).…”
Section: Us and Hispanic Cultural Orientations And Alcohol Usementioning
confidence: 99%
See 1 more Smart Citation
“…Raffaelli et al., ; Safer and Piane, ). On the other hand, enculturation can function as a protective factor against hazardous alcohol use (e.g., Daniel‐Ulloa et al., ; Graves, ; Marsiglia et al., ; Montoya et al., ) possibly because enculturation helps to buffer against the negative impact of acculturative stress.…”
Section: Alcohol Use and Acculturation Among Hispanic Americansmentioning
confidence: 99%
“…With respect to a risky drinking practice like drinking games participation, another study found that cultural practices with respect to U.S. acculturation and enculturation were associated positively and negatively, respectively, with frequency of drinking games participation and alcohol consumption for women, but not for men (Schwartz, Zamboanga et al, 2014). In short, while some research indicates that gender moderates the association between acculturation and drinking behaviors, not all bidimensional studies support this contention (Cano et al, 2015b; Montoya et al, 2016; Schweizer, Doran, Roesch, & Myers, 2011), thus raising continued questions about the effects of gender on these associations.…”
Section: Acculturation and Drinking Behaviorsmentioning
confidence: 99%